The effects of wildfire on lotic macroinvertebrate communities in Portugal - Machado, Ana Luísa Felgueiras de Brito (2015)
The effects of wildfires in Mediterranean lotic communities are still poorly documented. Despite some progress in recent years, the published data refer mainly to studies conducted in North America, with little information on European rivers. Given the importance of regional geographic context, both on the effects of fire and on the resilience of the communities, the gap in the biogeographical knowledge represent a limitation to the implementation of appropriate management measures. This thesis consists in a systematic study of the effects of fire on the macroinvertebrate communities of streams of North and Central Portugal. A chronosequence survey was conducted in order to analyze long-term effects of wildfires (1-18 years) and provide chronological information on the ecological recovery of macroinvertebrate communities. The results indicated that the macroinvertebrate communities recover in abundance and taxa richness and in terms of community structure about two years after the fire impact. A short-term survey was also carried out, where the initial response of macroinvertebrates to fire disturbance was documented, in streams recently affected by wildfires. The parameters analyzed were compared with reference sites without fire impact for the last 20 years. In all sampling periods, lower abundance and lower species richness were recorded in impacted streams, and differences in community structure were found between burnt sites and reference sites. In our study, both on long -term and short-term surveys, the environmental features that conditioned the response of biological communities were evaluated. River size, the extent of the burnt area, conductivity, along with channel characteristics and riparian vegetation, were considered determinant in the response of macroinvertebrates communities to fire impact, and can influence the susceptibility of stream ecosystems. We also analyzed the data of the short-term survey on a trait approach. Differences on functional diversity and on frequency of several trait modalities were analyzed. Specific differences in the food group and reproductive strategies between burned and not burned sites were recorded. Despite the unequivocal negative impact of wildfire on macroinvertebrate communities of Portuguese streams, the recovery seems to be rapid, demonstrating their resilience to this type of disturbance.